Incidence and severity of Arcanobacterium pyogenes injection site abscesses with needle or needle-free injection methods - Gerlach, B.M.; Houser, Terry A.; Hollis, Larry C.; Tokach, Michael D.; Nietfeld, Jerome C.; Higgins, James J.; Anderson, Gary Allen; Goehring, B.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 198 nursery age pigs were used to evaluate the difference in the occurrence of injection site abscesses between needle-free jet injection and conventional needle-and-syringe injection systems. Pigs were fed for 21 d prior to treatment administration to acclimate the pigs to the environment of the Kansas State University Segregated Early Weaning Unit. On d 21, each pig received 4 injections of aluminum hydroxide adjuvant, 1 in the neck and 1 in the ham by needle-free jet injection (Pulse Needle-Free Systems, Lenexa, KS) on 1 side and 1 in the neck and 1 in the ham on the opposite side by conventional needle-and-syringe injection. Immediately prior to injection, the external surface of the injection sites was contaminated with an inoculum of Arcanobacterium pyogenes. The pigs were then fed for a period of 27 and 28 d. On d 27 and 28, the pigs were humanely euthanized and sent to the Kansas State University Veterinary Diagnostics Laboratory, where necropsies were performed and the injection sites underwent histopathological evaluation. The needle-free jet injection system was associated with more injection site abscesses than the conventional needle-and-syringe injection method for both the neck (P = 0.06) and ham (P = 0.03) injection sites. Twelve abscesses were found at needle-free injection sites, whereas only 1 abscess was found where a conventional needle injection method was used. Five abscesses were found at the neck injection sites, and 8 abscesses were observed at the ham injection sites. Of the 13 abscesses found, 10 developed on the left side of the animal, and only 3 were on the right side. In summary, the implementation of needle-free jet injection systems in market hog production will be beneficial by eliminating the potential for needles and needle fragments in meat products, but it may increase the occurrence of injection site abscesses in pork carcasses that will need to be trimmed in pork processing plants.
Keywords: Abscess; Arcanobacterium pyogenes; Needle-free injection; Swine